The Racial Experiment - Warner, Susan C.; Mickle, Millicent (Challenges of Multicultural Education, 2005)
Mimi Mickle introduces a topic that proved to be the heartbeat of the evening and asked each student to discusses what they had been taught at home about racial relations. Students commented on the racial interaction of the facilitators. The Black facilitator was the political conservative, a Republican party organizer. The White facilitator was the liberal. Susan felt this last time together with Wilberforce students was the least productive of the three attempts. Susan shows the video Tuskegee that documents the hideous experiment imposed on a group of poor, African American men in Georgia when they were used as guinea pigs in a syphilis study. Students will also be required to visit two different websites: "pictorial tour of the civil rights movement with pictures and information from the key events" and "Without Sanctuary: Artifacts of Lynching in America" provide students with a firm grasp of the history and biography of African Americans.